Politica senza partiti? Il voto per Bassolino e De Magistris a confronto - Francesco Amoretti; Fortunato Musella (QOE-IJES)
After the introduction of the direct election for the ltalian mayors in l993, the comune of Naples has become one of the most relevant example of the so called "metro politan spring". Antonio Bassolino obtained a quasi plebiscitary consensus thanks to his ambition program of radical change. After about twenty years from that experience, the local election of 20ll is also the first to follow the long Bassolino's government. Yet it provides significant common elements to the post-Tangentopoli municipal consultation, starting from the diffuse anti-party mood and the adverse criticism against past admini strations. The two elections are both cases for the construction of personal leadership and for the spread of a direct relationship between candidate and citizenship, in the fra mework of the dismissal of the traditional political parties. ln this article a comparison wil be proposed through an analysis of electoral data and newspapers articles, in order to underline similarities between the Bassolino's and De Magistris' victories and to re construct the context in which they occurred.